Research on the Deformation Mechanism and Directional Blasting Roof Cutting Control Measures of a Deep Buried High-Stress Roadway - Xiaojie Yang; Chenkang Liu; Honglei Sun; Songlin Yue; Yuguo Ji; Xingyu Zhang; Lin Hou (Shock and Vibration)
Affected by the mining activities of the working face, the surrounding rock of the roadway is easily deformed and destroyed. For deep buried roadways, the deformation and destruction of the surrounding rock is particularly prominent. Under the influence of in situ stress fluctuation, 3−1103 tailgate of the Hongqinghe coal mine was in a complex stress environment with a maximum stress exceeding 20 MPa. Affected by mining stress, the roadway behind the working face was seriously deformed. In order to alleviate the deformation of the roadway, directional blasting and cutting measures for the 3−1103 tailgate were adopted in this paper. The mechanism of crack propagation in single-row to three-hole directional blasting was revealed by numerical simulation. The blasted rock was divided into three regions according to the crack condition. The numerical analysis of the cutting heights of 0 m, 10 m, 12 m, and 14 m, respectively, showed the stress peaks of different cutting heights and the deformation law of the surrounding rock. The pressure relief effect was the best at 14 m cutting height. At this time, the peak stress was 39 MPa with the smallest roadway deformation. Based on numerical simulation and theoretical analysis results, engineering tests were carried out. Field monitoring showed that the deformation of the roadway was inversely proportional to the roof cutting height. The higher the cutting height is, the more preferential the roadway is to reach the stable state. It can be concluded that directional blasting can change the surrounding rock structure, control the deformation of the roadway, and play a role in pressure relief. It provides a new measure to control roadway deformation.